Assessing accuracy predictors in megatrend qualitative forecasting in the hospitality and tourism industry - Cercas, Francisco José Branco (2019)
Plenty of literature on megatrends escapes the logic of validation. Most publications on forecasting apply quantitative methods and the use of qualitative forecasting is scarce especially in the Hospitality and Tourism (H&T) industry, which is so sensitive to macro level factors. Alongside this, it is surprising that studies that explore the accuracy of such predictions are scarce which hampers the capacity to improve forecasting techniques. With this in consideration, the main goal of this study was to uncover the potential predictors of accuracy in qualitative forecasting sources in H&T. In order to do so, we identified and selected a set of documents that used qualitative forecasting methods to predict trends in H&T for the 1998-2008 period, and devised an empirical study that puts to test the expected trends against the test of time. With a panel of 14 experts in H&T that indicated what occurred in the aforementioned period, we computed a weighted score of accuracy for each document and classified it according to four potential causal variables (Explicit methods, Number of cites, Multisource, and Multimethod, thought of as indicators of forecasting quality). The model was tested with a fuzzy set qualitative comparative analysis (fs/QCA) which indicated that clarifying the qualitative forecasting methods (Explicit) and having multiple sources (Multisource) are the main predictors of the qualitative forecasting sources’ accuracy in H&T.